Machine learning-based analysis of English lateral allophones - Piotrowska, Magdalena; Korvel, Gražina; Kostek, Bożena; Ciszewski, Tomasz; Czyżewski, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
Automatic classification methods, such as artificial neural networks (ANNs), the k-nearest neighbor (kNN) and self-organizing maps (SOMs), are applied to allophone analysis based on recorded speech. A list of 650 words was created for that purpose, containing positionally and/or contextually conditioned allophones. For each word, a group of 16 native and non-native speakers were audio-video recorded, from which seven native speakers` and phonology experts? speech was selected for analyses
Keywords: allophones; audio features; artificial neural networks (ANNs); k-nearest neighbor (kNN); self-organizing map (SOM)